KAJIAN TEORI: PENGEMBANGAN BAHAN AJAR MODEL PROBLEM BASED LEARNING BERNUANSA STEM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Adinda Ratna Ningtyas (UPT Penerbitan Universitas Jember, 2022)
One of the efforts to help students improve their critical thinking ability is by using teaching materials using STEM nuanced Problem Based Learning models. The Problem Based Learning model is a learning model that is very suitable for use in student-centered learning processes to stimulate higher-order thinking and can improve students' critical thinking in real-world problem-oriented situations. STEM is a learning approach that combines two or more fields of science contained in STEM, namely Science, Technology, Engineering, and Mathematics. The research method used is Systematic Literature Review. This method focuses on gathering information relevant to the topic being studied. The results of the study show that the development of teaching materials using STEM-based Problem Based Learning models can improve students' critical thinking ability. The results of these study, can then be used as further research that is interesting to study, namely the process of developing teaching materials for Problem Based Learning models with STEM nuances to improve critical thinking ability. Keywords: Critical Thinking Ability, Problem Based Learning, STEM.